2015
DOI: 10.1177/0971355715586893
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Capital on Small Firm Performance in West Bengal

Abstract: Formal and informal networks empower small firms to generate social capital by forging network ties, building on trust and sharing a vision among stakeholders. It enables them to obtain necessary resources, support, information and knowledge, which may be otherwise inaccessible to them. This study analyses the impact of social capital on firm performance through the constructs of network ties, trust and shared vision while drawing a comparison between firms associated with formal and informal networking. An em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 53 publications
6
25
0
2
Order By: Relevance
“…Also, Manev et al (2005) pointed out that network ties have a significant influence on firm performance in emerging economies. Saha and Banerjee (2015) also concluded that networking is a significant element in firm performance. Manev et al (2005) argued that networking is an important element for emerging entrepreneurs because it helps a firm establish a network with external partners which may help to identify new opportunities and increase performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Manev et al (2005) pointed out that network ties have a significant influence on firm performance in emerging economies. Saha and Banerjee (2015) also concluded that networking is a significant element in firm performance. Manev et al (2005) argued that networking is an important element for emerging entrepreneurs because it helps a firm establish a network with external partners which may help to identify new opportunities and increase performance.…”
Section: Discussionmentioning
confidence: 99%
“…Both formal and informal network support are essential for enterprises to create the relationship with actors in their environment to gain essential resources, knowledge and support which cannot be accessed by them directly. Network ties, trust, and shared vision have been found to affect the performance of small firms by creating resources, providing knowledge and mounting new capabilities (Saha and Banerjee 2015). Firms try to establish different networks for different purposes.…”
Section: Network Ties and New Venture Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Pratono and Mahmood (2015) survey entrepreneurs' own network resources among small and medium sized businesses in Indonesia and found that entrepreneurial orientation may have either a positive or negative impact on firm performance by encouraging firms to be more effective and achieve greater performance or having a negative effect on firms with superior entrepreneurial orientation. Saha and Benerjee (2015) survey small businesses in West Bengal and found that the impact of social capital on firm performance is significantly greater in firms engaged in formal and informal networking in contrast to firms embedded only in the informal network. Zhao et al (2018) found that corporate culture promotion is negatively related to firm market value, positively related to innovation output and not significantly related to firm financial performance.…”
Section: Literaturementioning
confidence: 99%
“…Strong relationships are an economic activity that is socially and economically situated and embedded in personal and group social networks. According to Saha and Banerjee (2015), social capital has an important role in the sustainability of SMEs. The results of their study indicate how formal and informal networks empower small companies to produce social capital by utilizing network linkage, building trust, and sharing visions among stakeholders.…”
Section: Introductionmentioning
confidence: 99%